Kritik Kebangsaan terhadap Krisis Demokrasi dan Ketidakadilan Sosial: Analisis Filsafat Pancasila melalui Pendidikan Agama Islam - Istingadah Istingadah; Ahmad Muzakki (Program Studi Pendidikan Agama Islam STAI Senori Tuban, 2025)
This article examines national criticism of the crisis of democracy and social injustice in Indonesia through the lens of Pancasila philosophy from the perspective of Islamic education. The purpose of this study is to reaffirm the relevance of Islamic education as a moral force in building a civilized and normative approach, analyzing the thoughts of key figures as well as literature related to democracy, Pancasila, and Islamic education. The findings indicate that the democratic crisis is characterized by constitutional distortions and elite domination, while social injustice arises from structural inequality. Islamic education plays a crucial role in instilling the values of justice and social responsibility, thereby serving as a strategic foundation for realizing a just and dignified society.